ANTIBIOTIC PROPERTIES OF TANNIC ACID OBTAINED FROM THE RIND OF POMEGRANATE - GAVARRON, FF (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1941)
Antibiotic properties of extracts of pomegranate rind are due to tannic acid, which is to be suspected in other vegetable extracts of similar propensities
CIENC MEX
Keywords: ANTIBIOTIC, PROPERTIES, ACID , OBTAINED, RIND, POMEGRANATE; CIENCIAS MEDICAS; FARMACOLOGIA